See you in the piazza : new places to discover in Italy - Mayes, Frances (Crown, 2019)
The Roman Forum, the Leaning Tower, the Piazza San Marco: these are the sights synonymous with Italy. But such landmarks only scratch the surface of this magical country's offerings. In See You in the Piazza, Frances Mayes introduces us to the Italy only the locals know, as she and her husband, Ed, eat and drink their way through thirteen regions--from Friuli to Sicily. Along the way, she seeks out the cultural and historic gems not found in traditional guidebooks. Frances conjures the enchantment of the backstreets, the hubbub of the markets, the dreamlike wonder of that space between lunch and dinner when a city cracks open to those who would wander or when a mind is drawn into the pages of a delicious book--and discloses to us the secrets that only someone who is on intimate terms with a place could find.